1999
DOI: 10.1038/sj.bjc.6690539
|View full text |Cite
|
Sign up to set email alerts
|

p27KIP1 is abnormally expressed in Diffuse Large B-Cell Lymphomas and is associated with an adverse clinical outcome

Abstract: Cell cycle progression is regulated by the combined action of cyclins, cyclin-dependent kinases (CDKs), and CDK-inhibitors (CDKi), which are negative cell cycle regulators. p27 KIP1 is a CDKi key in cell cycle regulation, whose degradation is required for G1/S transition. In spite of the absence of p27 KIP1 expression in proliferating lymphocytes, some aggressive B-cell lymphomas have been reported to show an anomalous p27 KIP1 staining. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 55 publications
1
26
0
3
Order By: Relevance
“…Group 3 is composed of simultaneous detection of low/null p27 expression, increased p53 expression, and decreased Rb or p16 expression (three alterations: 11 cases). lecular networks regulating the cell cycle in malignancies provides valuable information for the understanding of the impaired regulation of these networks and permits further insight into oncogenesis (11,15,17,19,23,24,26,29,34,36). This approach was adopted in the present study to analyze the expression of p27 in relation with components of the p53 and Rb1 growth control pathways and the status of proliferation in 80 cases of DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…Group 3 is composed of simultaneous detection of low/null p27 expression, increased p53 expression, and decreased Rb or p16 expression (three alterations: 11 cases). lecular networks regulating the cell cycle in malignancies provides valuable information for the understanding of the impaired regulation of these networks and permits further insight into oncogenesis (11,15,17,19,23,24,26,29,34,36). This approach was adopted in the present study to analyze the expression of p27 in relation with components of the p53 and Rb1 growth control pathways and the status of proliferation in 80 cases of DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, RS parallels the immunohistochemical pattern of p27 immunoreactivity exhibited by most histologically aggressive lymphomas. 42,43,46,47 Due to the lack of p27 Kip1 gene gross aberrations as determined by Southern blot analysis, the p27 protein loss in RS could be explained by a post-translational mechanism, like an enhanced ubiquitin proteosome-mediated degradation, as has been described in MCL. 46 Whether this finding is an epiphenomenon of the high proliferative rate of RS cells or represents a relevant event in histologic transformation is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…During the course of tumorigenesis, there evidently is a selective advantage to preserving partial p27 expression, thus harnessing its ability to provide a growth advantage to the neoplasm Morosetti et al 1995;Pietenpol et al 1995;Ponce-Castaneda et al 1995;Spirin et al 1996;Fero et al 1998). (4) Clinical studies investigating the subcellular localization of p27 in tumors suggest that while the loss of nuclear p27 is commonly observed, mislocalization of p27 to the cytoplasm of tumor cells is correlated with high tumor grade and poor prognosis (Nakasu et al 1999;Saez et al 1999;Sanchez-Beato et al 1999;Slingerland and Pagano 2000;Philipp-Staheli et al 2001;Kouvaraki et al 2002;Liang et al 2002;Besson et al 2004a;Rosen et al 2005;Qi et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some studies have indicated that p27 levels in tumors do not always correlate with proliferative index, and increasing evidence points to the importance of the subcellular localization of p27 in the control of its function, with cytoplasmic localization being a negative prognostic factor in certain instances (Singh et al 1998;Nakasu et al 1999;Saez et al 1999;Sanchez-Beato et al 1999;Slingerland and Pagano 2000;Philipp-Staheli et al 2001;Kouvaraki et al 2002;Liang et al 2002;Besson et al 2004a;Rosen et al 2005;Qi et al 2006). This possibility is supported by in vivo studies: p27 +/− mice are more susceptible to tumor development than p27 −/− animals in mammary and prostate tumor models, suggesting an active contribution of the remaining p27 allele (Muraoka et al 2002;Gao et al 2004).…”
mentioning
confidence: 99%